Why frightening imaginary worlds? Morbid curiosity and the learning potential of horror. (18th November 2022) - Scrivner, Coltan; Clasen, Mathias
Abstract: In addition to satisfying a predisposition for exploration, fiction with imaginary worlds may also appeal to morbid curiosity, an adaptive motivation to seek out information about dangerous situations. Most imaginary worlds contain narrative elements of danger, and immersion in such worlds may provide people with information that would be costly to acquire in the real world.